Democratic governance in Latin America - Mainwaring, Scott, 1954-; Scully, Timothy (Stanford University Press, 2010)
Producing more effective governance is the greatest challenge that faces most Latin American democracies today-a challenge that involves not only strengthening democratic institutions but also increasing governmental effectiveness. Focusing on the post-1990 period, this volume addresses why some policies and some countries have been more successful than others in meeting this dual challenge. Two features of the volume stand out. First, whereas some analysts tend to generalize for Latin America as a whole, this group of authors underscores the striking differences of achievement amo.